CLINICAL EVALUATION OF TECHNETIUM-99M LABELLED HUMAN POLYCLONAL IMMUNOGLOBULIN G FOR MUSCULOSKELETAL INFECTION - SRITARA, Chanika; SINPHURMSUKSKUL, Opas; BOONKITTICHAROEN, Vipa; MULPRUK, Pornchai; SIRISRIRO, Rojana; CHOKESUWATTANASKUL, Payap; PUCHINDA, Daungpen; Ngonrath Na AYUDHYA, Anna; CHOUPLYWECH, Putthiporn; KRIPHIBUL, Puangtong (The ASEAN Journal of Radiology, 2023)
BACKGROUND: Three-phase bone scan is highly sensitive in detecting infection of the musculoskeleton. However, its low specificity necessitates the search for a more definite measure. This study was designed to determine the sensitivity and the specificity of 99mTc- labelled polyclonal human IgG (HIG) for the detection of infection of the musculoskeleton and to compare these to that of conventional three-phase bone scintigraphy. METHODS: Thirty-four patients with suspected infection of the musculoskeleton underwent 99mTc-labelled polyclonal human IgG (HIG) scintigraphy 48 hours after 3-phase bone scintigraphy. Both scans were graded on a five-point scale by visual interpretation. The final diagnosis was established by means of bacteriologic culture, histopathologic analysis of surgical specimen or clinical follow-up (follow-up time of 28 ±13 months). There were 44 sites evaluated. Receiver operating characteristic (ROC) curve analysis was generated for both modalities. RESULTS: At their optimal threshold levels (score 33) of the HIG scan, the sensitivity, specificity, accuracy, likelihood ratios and area under the ROC curve were 84.61%, 96.77%, 93.18%, 26.23, and 0.967, respectively, while those of the 3-phase bone scan were 100%. 87.10%. 90.70%, 7.75, and 0.941, respectively. No adverse reaction was encountered.